Correlation of surface-enhanced Raman spectroscopic fingerprints of kidney transplant recipient urine with kidney function parameters - Zhongli Huang (Nature Portfolio, 2021)
Abstract Routine monitoring of kidney transplant function is required for the standard care in post-transplantation management, including frequent measurements of serum creatinine with or without kidney biopsy. However, the invasiveness of these methods with potential for clinically significant complications makes them less than ideal. The objective of this study was to develop a non-invasive tool to monitor the kidney transplant function by using Surface-Enhanced Raman Spectroscopy (SERS). Urine and blood samples were collected from kidney transplant recipients after surgery. Silver nanoparticle-based SERS spectra of the urine were measured and evaluated using partial least squires (PLS) analysis. The SERS spectra were compared with conventional chemical markers of kidney transplant function to assess its predictive ability. A total of 110 kidney transplant recipients were included in this study. PLS results showed significant correlation with urine protein (R 2 = 0.4660, p < 0.01), creatinine (R 2 = 0.8106, p < 0.01), and urea (R 2 = 0.7808, p < 0.01). Furthermore, the prediction of the blood markers of kidney transplant function using the urine SERS spectra was indicated by R 2 = 0.7628 (p < 0.01) for serum creatinine and R 2 = 0.6539 (p < 0.01) for blood urea nitrogen. This preliminary study suggested that the urine SERS spectral analysis could be used as a convenient method for rapid assessment of kidney transplant function.